Pengaruh Bauran Pemasaran Terhadap Perilaku Konsumen Produk Bawang Merah Goreng Di Kabupaten Nganjuk - Rahmadhani, Ika Puspitasari Dyah; Daroini, Ahsin; Talkah, Abu (Universitas Islam Kadiri, 2024)
The marketing mix is a component consisting of product, price, promotion, and place, as attributes attached to a product that is used as a consumer attraction. The consumer attraction referred to in this study is the influence of the marketing mix on consumer behavior of fried shallot products in Nganjuk Regency. Consumer behavior is related to the marketing mix variables that are taken into consideration by consumers to make purchasing decisions. If the marketing mix variables can be analyzed and known, then consumer satisfaction and behavior will be managed properly. This research is a descriptive quantitative study that aims to analyze the effect of product, price, promotion, and distribution channel variables on consumer behavior of Fried Onion products in Nganjuk Regency. The variable of the influence of the marketing mix on consumer behavior was obtained based on the results of the questionnaire assessment by Fifty respondents as consumers of fried shallots in Nganjuk Regency, each variable has six statements with a Likert scale rating based on the sum of the attitudes of respondents in responding to statements related to the variables be measured. The results of the assessment were analyzed using the Multiple Linear Regression method, using the SPSS program, where all the variable values obtained were entered to find the effect of the independent variables, namely product (X1), price (X2), promotion (X3) and place (X4) on the dependent variable through consumer behavior regression (Y). Through this analysis, it was found that the product and price variables of fried shallots in Nganjuk Regency did not show significant results. While the place variable shows has the most significant effect. While each of these variables, the significance value affects each other, so that it simultaneously affects the consumer behavior of fried shallot products in Nganjuk Regency.